Engaging comparative urbanism : art spaces in Beijing and Berlin - Ren, Julie (Bristol University Press, 2021)
Ren examines the making of art spaces in Beijing and Berlin to engage with comparative urbanism as a framework for doing research. Across vastly different contexts where universal theories of modernity or development seem increasingly misplaced, the concept of aspiration provides an alternative lens to understand the nature of urban change.